2009
DOI: 10.1111/j.1466-8238.2009.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of changes in climate and forest cover on mortality and growth of the southernmost European fir forests

Abstract: AimsThe combined effects of changes in climate and land use on tree mortality and growth patterns have rarely been addressed. Relict tree species from the Mediterranean Basin serve as appropriate models to investigate these effects, since they grow in climatically stressed areas which have undergone intense cover changes. The aim is to use climate, aerial photographs, stand structure and radial-growth data to explain the mortality and historical patterns of growth of Abies pinsapo in the area where this relict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 35 publications
8
116
0
19
Order By: Relevance
“…One of the fundamental principles of dendroecology and dendroclimatology is that tree populations in marginal regions are more sensitive to climate than those in core regions, with more interannual variability in growth and stronger relationships between growth and limiting climate factors, particularly summer drought (Fritts 1966). This principle has been demonstrated for conifers (Carrer et al 2010;de Luis et al 2013;Linares et al 2009) and also to a more limited extent in broadleaved species such as F. sylvatica, although research has focused on elevation transects or regional networks of sites. For example, studies have shown that F. sylvatica at low elevations is more sensitive to summer drought than at high elevations (Di Filippo et al 2007;Hartl-Meier et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One of the fundamental principles of dendroecology and dendroclimatology is that tree populations in marginal regions are more sensitive to climate than those in core regions, with more interannual variability in growth and stronger relationships between growth and limiting climate factors, particularly summer drought (Fritts 1966). This principle has been demonstrated for conifers (Carrer et al 2010;de Luis et al 2013;Linares et al 2009) and also to a more limited extent in broadleaved species such as F. sylvatica, although research has focused on elevation transects or regional networks of sites. For example, studies have shown that F. sylvatica at low elevations is more sensitive to summer drought than at high elevations (Di Filippo et al 2007;Hartl-Meier et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of climate change on vegetation are likely to vary regionally and will result from a combination of stress factors, including elevated temperatures [3], reduction of rainfall [4], and shifts in wildfire regimes [5]. Furthermore, the consequences of these new conditions will be modulated by biotic factors and direct human impacts on forests (e.g., management) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates an increase of forest decline in Iberian woodlands (Martínez-Vilalta and Piñol, 2002;Linares et al, 2009;;Hereş et al 2012;Carnicer et al, 2011;. Nevertheless, the increase in oak mortality occurring in our study region is, to our knowledge, the first case in the Iberian Peninsula of massive population-level die-off threatening the sustainability of a forest ecosystem.…”
Section: Climate Change Could Have Determined the Inception Of The Momentioning
confidence: 65%